Pengaruh Ukuran Perusahaan Dan Leverage Terhadap Nilai Perusahaan Dengan Profitabilitas Sebagai Variabel Intervening (Studi Pada Perusahaan Sektor Industri Barang Konsumsi) - Pemy Christiaan (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2022)
This study aims to determine the effect of firm size and leverage on profitability and firm value, and examine the mediating effect of firm size and leverage on firm value through profitability. This research was conducted in the Consumer Goods Industry sector companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2019 period, taking 38 companies as research samples. The results showed that the size of the company had a significant effect on profitability. Leverage has a significant effect on profitability. Firm size has a significant effect on firm value. Leverage has a significant effect on firm value. Profitability has a significant effect on firm value. However, based on the Sobel test, the profitability results were able to mediate firm size to firm value. But profitability is not able to mediate leverage to firm value